Cerebral Representation of Sound Localization Using Functional Near-Infrared Spectroscopy - Tian, Xuexin; Liu, Yimeng; Guo, Zengzhi; Cai, Jieqing; Tang, Jie; Chen, Fei; Zhang, Hongzheng (Frontiers in Neuroscience, 2021)
Sound localization is an essential part of auditory processing. However, the cortical representation of identifying the direction of sound sources presented in the sound field using functional near-infrared spectroscopy (fNIRS) is currently unknown. Therefore, in this study, we used fNIRS to investigate the cerebral representation of different sound sources. Twenty-five normal hearing subjects (aged 26 ± 2.7, male 11, female 14) were included and actively took part in a block design task. The test setup for sound localization was composed of a 7-speaker array spanning a horizontal arc of 180° in front of the participants. Pink noise bursts with two intensity levels (48 dB/58 dB) were randomly applied via five loudspeakers (-90°/-30°/-0°/+30°/+90°). Sound localization task performances were collected, and simultaneous signals from auditory processing cortical fields were recorded for analysis by using a support vector machine (SVM). The results showed a classification accuracy of 73.60%, 75.60%, 77.40% on average at -90°/0°, 0°/+90°, and -90°/+90° with high intensity, and 70.60%, 73.6%, 78.6% with low intensity. The increase of oxyhemoglobin was observed in the bilateral nonprimary auditory cortex (AC) and dorsolateral prefrontal cortex (dlPFC). In conclusion, the oxyhemoglobin (oxy-Hb) response showed different neural activity patterns between the lateral and the front sources in the AC and dlPFC. Our results may serve as a basic contribution for further research on the use of fNIRS in spatial auditory studies.